The Association of Volunteer Motivation and Thriving at Work of College Students During COVID-19: Job Burnout and Psychological Capital as Mediators - Li, Jun; Ge, Cao; Li, Shiyi (Frontiers in Public Health, 2022)
Thriving at work is a type of mental state in which an individual feels vigorous and learning at the same time in the job. Previous studies have shown that individual internal motivation is relevant to thriving at work and volunteer behaviors, but the role of motivation is still to be further explored. Based self-determination theory, this study focuses on the mediating effects of job burnout and psychological capital on the relationship between volunteer motivation and thriving at work. 349 college student volunteers who participated in psychological assistance volunteer activities during the COVID-19 pandemic were investigated using the Volunteer Function Motivation Inventory, Maslach Burnout Inventory, PsyCap Questionnaire and Thriving at work scale. The results indicated that job burnout and psychological capital mediate the relationship between volunteer motivation and thriving at work. The results not only offer important theoretical insights of Volunteer Motivation and Thriving at Work, but also generate practical implications regarding how to use motivating Volunteer behavior and enhanced well-being at work.